Komunikasi Transaksional dalam Project Based Learning di SMA MBS Zam-Zam Muhammadiyah Banyumas - Ika Dian Nur Rizki; Musa Musa; Muridan (Yayasan Al-Afif, 2026)
This study evaluates the transformation of communication models from linear to transactional through the implementation of Project-Based Learning (PjBL) at SMA MBS Zam-Zam Muhammadiyah Banyumas, aimed at addressing low student motivation. Using a descriptive qualitative approach with a case study method, data were gathered through participant observation, documentation, and literature reviews of four primary projects: folklore drama performances, biography writing, book reviews, and potentialsite observations at Situ Elok. The findings reveal that PjBL implementation successfully dismantled the